Bird [compact disc, unabridged] - Johnson, Angela, 1961- (Random House/Listening Library, 2004)
Devastated by the loss of a second father, thirteen-year-old Bird follows her stepfather from Cleveland to Alabama in hopes of convincing him to come home, and along the way helps two boys cope with their difficulties.